2010
DOI: 10.1002/dvg.20639
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish sp7:EGFP: A transgenic for studying otic vesicle formation, skeletogenesis, and bone regeneration

Abstract: Summary We report the expression pattern and construction of a transgenic zebrafish line for a transcription factor involved in otic vesicle formation and skeletogenesis. The zinc finger transcription factor sp7 (formerly called osterix) is reported as a marker of osteoblasts. Using bacterial artificial chromosome (BAC)-mediated transgenesis, we generated a zebrafish transgenic line for studying skeletal development, Tg(sp7:EGFP)b1212. Using a zebrafish BAC, EGFP was introduced downstream of the regulatory reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
143
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 45 publications
1
143
0
Order By: Relevance
“…Alizarin red staining in tiny larva is a fine and complicated procedure, and it only reflects bone mineralization. In tg(sp7:egfp), osteoblasts are specifically marked by GFP, which make osteoblasts visible [24][25][26] . Osteoblast differentiation and bone formation in tg(sp7:egfp) can be directly monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alizarin red staining in tiny larva is a fine and complicated procedure, and it only reflects bone mineralization. In tg(sp7:egfp), osteoblasts are specifically marked by GFP, which make osteoblasts visible [24][25][26] . Osteoblast differentiation and bone formation in tg(sp7:egfp) can be directly monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2006, when Fleming et al [21] found that wild-type larval zebrafish exposed to prednisolone showed an obvious delay of skull mineralization based on alizarin red staining, zebrafish larvae have been widely used for the highthroughput screen for anti-osteoporotic candidates [22,23] . Tg (sp7:egfp) is a transgenic line zebrafish characterized by the osterix gene driven expression of green fluorescent protein (GFP) in osteoblast differentiation [24,25] . Because GFP-positive osteoblasts are visible in tg(sp7:egfp) larvae, the process of osteoblast differentiation and bone formation can be directly monitored via alteration of GFP fluorescence intensity using a fluorescence microscope.…”
Section: Original Articlementioning
confidence: 99%
“…Zebrafish lines include ihha hu2131 (Hammond and Schulte-Merker, 2009), Tg(Has.RUNX2: EGFP) zf259 (Kague et al, 2012), Tg(sp7:EGFP) b1212 (DeLaurier et al, 2010), Tg(col2a1a BAC :GFP) el483 (Askary et al, 2015), Tg(Ola.Sp7: CreERT2-P2A-mCherry) (i.e. sp7:mCherry) and Tg(Ola.Osteocalcin.1: EGFP) (Knopf et al, 2011).…”
Section: Zebrafish Strainsmentioning
confidence: 99%
“…Understanding how salamanders regenerate limbs should provide critical insight into efforts to stimulate these processes in vertebrates that do not regenerate limbs, yet the list of modern molecular genetic tools that can be applied to salamanders is currently very short. Other model systems with a much more sophisticated experimental toolkit, such as zebrafish, have provided valuable clues to the molecular underpinnings of vertebrate appendage regeneration (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, fin regeneration in teleost fish (such as zebrafish) is not completely analogous to limb development or regeneration.…”
mentioning
confidence: 99%